The philosophy of decoration in Islamic architecture - Omer, Spahic (Kulliyyah of Architecture and Environmental Design, IIUM, 2009)
This book discusses the philosophy of decoration in Islamic architecture. The book, however, is not written from a pure architecture perspective. The nature of its studies is a philosophical or conceptual rather than a empirical one. The book is divided into five chapters. The first two chapters, namely “The Concept of Decoration in the Holy Qur'an and in the Prophet's Sunnah” and “Islam and Beauty”, constitute what could be described as conceptual framework for the theme at hand. Since the subject of Islamic decoration in this book is viewed, mainly, through the prism of architecture, dwelling on the issue of significance of building pursuits in Islam is rather essential. This covered in third chapter which entitled “Islamic on Erecting Buildings”. The fourth and fifth chapters, entitled “Islamic Decoration as an Instrument of Worship” and “Man–Made ‘Signs' amid the Sign of God in Nature” respectively, represent the core of the book. In them the subject of the philosophy of Islamic decorative arts in architecture is discussed directly and thoroughly from different perspective. Out of the many objective that could be achieved by undertaking this kind of a study, the following list presents the main objectives of this book: